Gossip as a Channel for Circulating Subversive Truth: In Heym's The King David Report, the GDR and the Jardin du Luxembourg - Fishelov, David (Nouvelle Revue Synergies Canada, 2014)
In The King David Report (1972), Stefan Heym (1913-2001) offers a favorable view of gossip, notwithstanding biblical censuring of that activity (e.g. Proverb 11:13). Heym's satirical re-telling of the biblical story focuses on the character of Ethan, a writer-historian appointed by King Solomon to compose an official report on the life and rise to power of King David. At one point Ethan's two sons, Shem and Sheleph, come back from the market, telling Ethan of some "juicy" rumors they heard there. These rumors, while using some exaggerations and added embellishments, nevertheless provide insights into the political situation much more faithful to the truth than the fabrications of official spokespersons. To substantiate Heym's literary portrayal of gossip as a channel for communicating subversive truth in authoritarian regimes, I cite Robert Darnton's systematic historical research into the diverse channels for communicating news in Paris of the eighteenth century (Darnton, 2000).